Applying the emergency risk management process to tackle the crisis of antibiotic resistance - Dominey-Howes, Dale; Bajorek, Beata; Michael, Carolyn A.; Betteridge, Brittany; Iredell, Jonathan; Labbate, Maurizio (Frontiers in Microbiology, 2015)
We advocate that antibiotic resistance be reframed as a disaster risk management problem. Antibiotic resistant infections represent a risk to life every bit as significant as other commonly occurring natural disasters (e.g. earthquakes). Despite significant efforts by global health authorities, antibiotic resistance continues to escalate. Therefore, new approaches and expertise are needed to manage the issue. In this perspective we: (1) make a novel call for the emergency management community to recognise the antibiotic resistance risk and join in addressing this problem; (2) suggest using the risk management process to help tackle antibiotic resistance; (3) show why this approach has value and why it is different to existing approaches; and (4) identify public perception of antibiotic resistance as an important issue that warrants exploration.